Effects of Thrombolytic Therapy on blood pressure and heart rate variations, 24h after Acute Myocardial Infarction in Hypertense Individuals - Mendoza Paulini, Aurelio (1998)
The aim of this descriptive, comparative study was to describe the variations in blood pressure (BP) and heart rate (HR) immediately after acute myocardial infarction (AMI) in patients with hypertension threated with thrombolysis for AMI and those which didn‘t receive thrombolytic therapy. We hypothetized that both, prior hypertensive BP values and circadian variations, will return to their baseline (hypertensive) levels in patients who underwent thrombolysis, showing a reperfusion of involved area and an abolition of baroreflex effects on BP and HR. Of all patients referred to the Hospital Nacional Arzobispo Loayza between may 1996 and may 1997, we investigated 16 hypertense patients with AMI, thrombolyzed with streptokinase; and 15 hypertense patients with AMI, but who didn‘t undergo thrombolysis, as controls. We considered the results of PAMELA study as comparative values. The mean HR values of thrombolyzed patients showed non significant differences with respect to the controls, either in day (78 ± 9,7 vs. 72 ± 13 beats/min, p = 0,4061) or night (79 ± 12,9 vs. 69 ± 10 beats/min, p = 0,5869). BP also failed to show significant differences respect to the controls in 24-hour average (128/79 vs. 121/75 mmHg); 14-hour (day) average (127/79 vs. 124/78 mmHg); and 10-hour (night) average (128/78 vs. 118/71 mmHg (p > 0,05 for all)). We concluded that there were no circadian variations in BP and HR values from hypertense patients with AMI who underwent thrombolytic therapy. BP values were lower than those from PAMELA study in thrombolyzed and non-thrombolyzed patients.